Antibacterial effectiveness test of red dragon fruit seed extract (Hylocereus costaricensis) Inhibiting The Growth of Porphyromonas gingivalis on acrylic resin plates: Study experimental - Ardinata, Nadya; Ferdina, Resa; Amran, Ricky (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACT  Introduction: Tooth loss can affect a person's quality of life, including speech function and nutritional intake. The use of acrylic resin dentures carries a risk of plaque accumulation, which can be a breeding ground for pathogenic bacteria such as Porphyromonas gingivalis. This study aims to analyze the effectiveness of red dragon fruit seed extract (Hylocereus costaricensis) as a natural antibacterial alternative. Methods: This study used a post-test-only control group experimental design. The sample used was a 10 x 10 x 1 mm acrylic resin plate. Red dragon fruit seed extract was tested at concentrations of 5%, 10%, and 15%. Data analysis was carried out using the One Way ANOVA test. Results: Red dragon fruit seed extract  (Hylocereus costaricensis (F.A.C Weber) Britton & Rose) was effective in inhibiting the growth of Porphyromonas gingivalis. The 15% concentration demonstrated the lowest bacterial growth compared to other concentrations. The results of the One Way ANOVA test in this study showed a significant difference between treatment groups, with a p-value of 0.000 (p < 0.05), indicating that the administration of red dragon fruit seed extract at various concentrations had a significant effect in inhibiting the growth of Porphyromonas gingivalis.Conclusion: Red dragon fruit seed extract has potential as a natural antibacterial agent for preventing the growth of Porphyromonas gingivalis on acrylic resin plates. These findings provide a natural alternative for maintaining oral health in denture users. KEY WORDS: antibacterial, red dragon fruit seed extract, porphyromonas gingivalis, heat-polymerized acrylic resin.Uji efektivitas antibakteri ekstrak biji buah naga merah (Hylocereus costaricensis)  terhadap pertumbuhan porphyromonas gingivalis pada plat resin akrilik: Studi  eksperimentalABSTRAKPendahuluan: Kehilangan gigi dapat mempengaruhi kualitas hidup seseorang, termasuk fungsi bicara dan nutrisi. Penggunaan gigi tiruan yang berbahan dasar resin akrilik berisiko menyebabkan akumulasi plak, yang dapat menjadi tempat berkembang biaknya bakteri patogen seperti Porphyromonas gingivalis. Penelitian ini bertujuan untuk menganalisis uji efektivitas ekstrak biji buah naga merah (Hylocereus costaricensis) sebagai alternatif antibakteri alami. Metode: Penelitian ini menggunakan metode eksperimental dengan rancangan Posttest Only Control Group Design. Sampel yang digunakan adalah plat resin akrilik berukuran 10 x 10 x 1 mm. Ekstrak biji buah naga merah diuji pada konsentrasi 5%, 10%, dan 15%. Analisis data dilakukan dengan uji One Way ANOVA. Hasil: Ekstrak biji buah naga merah (Hylocereus costaricensis (F.A.C Weber) Britton & Rose), efektif dalam menghambat pertumbuhan Porphyromonas gingivalis. Konsentrasi 15% menghasilkan jumlah pertumbuhan bakteri terendah dibandingkan dengan konsentrasi lainnya. Hasil uji One Way ANOVA dalam penelitian ini menunjukkan adanya perbedaan yang signifikan antar kelompok perlakuan dengan nilai p = 0,000 (p < 0,05), yang menandakan bahwa pemberian ekstrak biji buah naga merah pada berbagai konsentrasi berpengaruh dalam menghambat pertumbuhan Porphyromonas gingivalis. Simpulan: Ekstrak biji buah naga merah memiliki potensi sebagai agen antibakteri untuk mencegah pertumbuhan Porphyromonas gingivalis pada plat resin akrilik. Temuan ini memberikan alternatif alami yang dapat digunakan untuk menjaga kesehatan mulut pada pengguna gigi tiruan.  KATA KUNCI: antibakteri, ekstrak biji buah naga merah, porphyromonas gingivalis, resin akrilik polimerisasi panas.